Development of E-Modules Based on Guided Inquiry to Improve Students' Critical Thinking Ability - Diska Evi Liana; Muzzazinah; Meti Indrowati (Nusantara Science and Technology Proceedings, 2022)
This type of research is development research that aims to determine the characteristics, feasibility, and effectiveness of the guided inquiry-based respiratory system E-module to improve students’ critical thinking ability. The development model used is research and development (RND), which refers to the Borg and Gall development model that has been modified and adapted to conditions in the field, consisting of nine stages: 1) Research and informing collecting, 2). Planning, 3) developing a preliminary form of product, 4) preliminary feed testing, 5) main product revision, 6) main field testing, 7) operational product revision, 8) operational field testing, 9) e-module final product. The data analysis technique used is the descriptive analysis which is used to describe the characteristics of the e-module to be developed, and the feasibility analysis of the e-module based on the N-gain score obtained. The results of the N-gain test score in the control class, which is 0.65, are included in the medium category, while for the experimental class the average N-gain score of 0.78 is included in the high category. Based on these results, E-modules based on guided inquiry are very feasible to be used in learning and have proven effective in improving students' critical thinking ability.